Augmented and virtual reality application in traditional architectural project presentation: Case study of 'MH Petra' house - Pejic, Petar; Krasic, Sonja; Veljkovic, Milica; Sakan, Srdjan; Rizov, Tashko (Centre for Evaluation in Education and Science (CEON/CEES), 2016)
The traditional method of architectural project presentations involves the use of a printed material on which the building is presented by using of two-dimensional drawings and images. The main problem is the presentation of three-dimensional space on two-dimensional paper. The development of smart portable devices with special sensors and greater processing power and contemporary methods of augmented and virtual reality motivated authors to investigate possibilities of their applications in architectural presentations. The main focus of the paper is the development of modern, portable systems for architectural project presentations which will be presented on a case study of the house. For this purpose, a method of virtual and augmented reality is used for upgrading traditional printed catalogue of the project. This approach enables easier and better understanding of all types of architectural objects and urban complex, allowing the user intuitive spatial overview of architectural work.
Keywords: Computer graphics; Virtual Reality; Augmented Reality; Architectural projects.